Spanish version of the Dossier ABRASCO on the impact of pesticides on health:: much more than a mere translation (Sustainability in Debate, 2018)
CARNEIRO, Fernando Ferreira (Org.)”¨Dossier ABRASCO: alerta sobre los impactos de los agrotóxicos en salud / Organización: Fernando Ferreira Carneiro, Lia Giraldo da Silva Augusto, Raquel Maria Rigotto, Karen Friedrich e André Campos Búrigo. Rio de Janeiro: EPSJV; São Paulo: Expressão Popular, 2016. Disponível em http://abrasco.org.br/dossieragrotoxicos/